Editor’s Note - Sewell, Ian (Current Musicology, 2019)
This special issue of Current Musicology brings together a number of scholars at various stages of their careers to reflect on issues of music pedagogy. The result encompasses a broad array of topics addressing different kinds of student. At the same time, this volume is the second to exhibit Current Musicology’s new format, where the lead article is a scholarly literature review on a musical topic. The new format, in time, is planned to replace the annual special issue, and each editor will work closely with the author of the lead article to offer a critical perspective on some relevant and ongoing issue or area of musicological interest—in short, on Current Musicology.